Aspectos ecológicos de las lagunas pampeanas y su posible influencia sobre las pesquerías del pejerrey: el caso de laguna El Coraje - Licoff, P. (2008)
El Coraje shallow lake is an arheic and semi permanent environment, located in SE of the Province of Buenos Aires, mainly dedicated to sport fishing. Precipitation cycles, alternating above and bellow the average, cause frequent changes in its area, currently highly reduced. The aim of this paper is to characterize the fish community of El Coraje shallow lake, and to determine the possible causes and consequences of the massive mortality inferred. A limnological and ichtiological sampling was made during April 2006, when the drought was extreme. Chemical analyses evidence ion concentration, including nutrients (total phosphorous = 1,454 ppm). Turbidity was high (Secchi disk = 14 - 18 cm) as well as chlorophyll- a (318 mg/m3). A bloom of Nodularia was observed, responsible for a scent similar to gamexane. Macrozooplanckton was abundant. The operations with trawl net became difficult due to the excess of accumulated sediment. Using the gill net, only pejerrey (Odontesthes bonariensis) could be found, and in a bad sanitary state. However, the k factor and relative weight didn’t show any link to recent affectations (except for a higher length). Specimens presented haemorrhages in eyes and body. All of them had their eyes affected of diverse way and degree, in some cases with total absence of the ocular globe. Metacercaries of Trematode in high numerosity were observed in brain. Fins presented different morphologic alterations, with loss of ratios, adjudged to bacterial diseases. A prevalence of Cestode and Nematode in high density was observed in the digestive tube. Moreover, in average 76 % of the tube was empty. Hence, there are many environmental variables (bacteria, ion concentration, phytoplankton blooms, etc.) that add up to affect the fish community and generate stress, causing fish mortality.